Vapour–liquid critical properties of components of biodiesel. 1. Methyl esters of n-alkanoic acids. (1st August 2015) - Nikitin, Eugene D.; Popov, Alexander P.
Highlights: Critical properties of seven n -alkanoic acid methyl esters were measured. These compounds are components of biodiesel. Equations for the estimation the critical properties of the esters were obtained. Abstract: The critical temperatures and the critical pressures of n -alkanoic acid methyl esters C n H2 n − 1 O2 CH3 with n  = 6, 7, 8, 9, 10, 11, 12 have been measured by the pulse-heating technique. These esters are components of biodiesel. Equations for the calculation of the critical temperatures and pressures of methyl esters of n -alkanoic acids have been obtained. The experimental critical properties have been compared with the estimations made by these equations and by the group contribution methods of Wilson and Jasperson, Marrero and Gani, and Nannoolal, Rarey, and Ramjugernath. The equations suggested in this study provide the best accuracy for the estimation of the critical properties of n -alkanoic acid methyl esters with n from 5 to 18; these equations can be used for the calculation of the critical constants of heavier esters. The acentric factors of n -alkanoic acid methyl esters have been estimated.